2004
DOI: 10.2746/0425164044877341
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between scintigraphic and radiographic evaluations of spinous processes in the thoracolumbar spine in riding horses without clinical signs of back problems

Abstract: Summary Reasons for performing study: Radiography and scintigraphy are used to aid diagnosis of the cause of back pain, but a large variation in appearance and radiopharmaceutical uptake in fully functioning horses make diagnosis difficult. Objectives: To describe the range of and compare scintigraphic and radiographic findings in the spinous processes of horses without clinical signs of back problems. Methods: Thirty‐three apparently normal riding horses underwent scintigraphic and radiographic examination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
112
3
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(127 citation statements)
references
References 15 publications
(38 reference statements)
9
112
3
3
Order By: Relevance
“…This standardised the intervertebral DSP distances and prevented over/under-estimation of the radiologic abnormalities of the DSPs. The location of radiologic abnormalities (mainly T14 -L2) was comparable with the previous reports (Jeffcott 1979(Jeffcott , 1980Townsend 1986;Kreling 1996;Haussler 1999, Erichsen 2004). …”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This standardised the intervertebral DSP distances and prevented over/under-estimation of the radiologic abnormalities of the DSPs. The location of radiologic abnormalities (mainly T14 -L2) was comparable with the previous reports (Jeffcott 1979(Jeffcott , 1980Townsend 1986;Kreling 1996;Haussler 1999, Erichsen 2004). …”
Section: Discussionsupporting
confidence: 90%
“…The lack of association between age and impinging spinous processes in our study was comparable to some previous studies (Jeffcott 1979, Haussler 1999, but was contradictory to the result of others (Erichsen 2004, Zimmerman 2011, Geiger 2015. Zimmerman et al (2011) found that horses with thoracolumbar pain were significantly older than those without pain.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Les lésions les plus fréquentes sont représentées par les conflits et chevauchements des PE (Jeffcott 1980 ;Erichsen et al 2004;Denoix & Dyson 2011 ;Zimmerman et al 2011Zimmerman et al et 2012. Cette entité pathologique regroupe différent types de lésions: rétré-cissement de l'espace inter-épineux, conflits, voire chevauchement des PE et desmo/enthésopathies du ligament inter-épi-neux.…”
Section: Processus éPineux (Pe)unclassified
“…L'examen échographique a un inté-rêt moindre et peut être employé pour détecter un contact, des remodelages et remaniements, voire un défaut d'alignement des PE. La scintigraphie montre dans la plupart des cas une excellente corrélation avec les données radiographiques: à la fois pour la localisation et la sévérité des anomalies (Denoix & Dyson 2011 ;Zimmerman et al 2011 (Erichsen et al 2004). …”
Section: Processus éPineux (Pe)unclassified